PEMBUATAN MESIN PENGADUK ADONAN UNTUK MENINGKATKAN PRODUKSI PADA USAHA KECIL PENJUAL MARTABAK - Widodo, Rahmat Doni; Khumaedi, Muhammad (Rekayasa : Jurnal Penerapan Teknologi dan Pembelajaran, 2017)
This Â devotion Â activity Â carried Â out Â with Â the Â aim Â to Â help Â problems Â that Â were Â be- ingÂ  facedÂ  byÂ  smallÂ  businessÂ  sellerofÂ  martabakÂ  â€œBangkaâ€. ActivityÂ  specific targetÂ  ofÂ  thisÂ  de- votionÂ  isÂ  toÂ  generateÂ  theÂ  externalÂ  aspectsÂ  ofÂ  productionÂ  suchÂ  as:Â  makingÂ  doughÂ  mixer machine of sweet martabak that is rotated with electric motor. The methods used for the imple- mentation of this activity was done in various ways that support each other, namely: coordina- tion, machine building, training of machine operating, accompanying partners during the ac- tivities in progress and evaluating activity results. The result of this devotion activity is dough stirring machine with Â¼ PK that time of the stirring becomes five times faster, stirring dough results Â become Â smoother, Â production Â increases, Â as Â well Â as Â income Â and Â increasing Â its Â profits